(untitled) - Bonds, Mark Evan; Neal, Jocelyn R (Upper Saddle River, 2009)
Includes bibliographical references and index
Keywords: Music appreciation; Music -- History and criticism; Âm nhạc -- Lịch sử và phê bình; Đánh giá âm nhạc